2017
DOI: 10.1111/nep.12832
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of self‐reported quality of life for an Australian haemodialysis and haemodiafiltration cohort

Abstract: This study has demonstrated that younger age and comorbid diabetes were responsible for a statistically significant reduction in quality of life, and HDF did not confer any advantage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The CONvective TRAnsport STudy (CONTRAST) study did not find a significant difference between the two treatment modalities through the Kidney Disease Quality of Life 36-Item short form survey (KDQoL SF-36) questionnaire. 18 Small cross-over studies comparing HD to HDF have shown various results: some did not find any significant difference in quality of life between groups, 19 , 20 whereas others found HDF to be beneficial in regard to “bodily pain” and “role limitations due to emotional functioning,” 15 and to be associated with better score on KDQoL SF-36 compared with HD. 21 More recently, Smith et al, 22 in a randomized, single-blind, cross-over study comparing high-flux HD with HDF, reported similar recovery time and quality of life scores, through KDQoL SF between groups.…”
Section: Discussionmentioning
confidence: 99%
“…The CONvective TRAnsport STudy (CONTRAST) study did not find a significant difference between the two treatment modalities through the Kidney Disease Quality of Life 36-Item short form survey (KDQoL SF-36) questionnaire. 18 Small cross-over studies comparing HD to HDF have shown various results: some did not find any significant difference in quality of life between groups, 19 , 20 whereas others found HDF to be beneficial in regard to “bodily pain” and “role limitations due to emotional functioning,” 15 and to be associated with better score on KDQoL SF-36 compared with HD. 21 More recently, Smith et al, 22 in a randomized, single-blind, cross-over study comparing high-flux HD with HDF, reported similar recovery time and quality of life scores, through KDQoL SF between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Self-reported quality of life (QoL) Measuring QoL was highly subjective because it depended on self-reported answers [27]. QoL contained multiple domains [1], but scholars agreed that a one-dimensional measure was adequate to represent it for large-scale surveys [28].…”
Section: Methodsmentioning
confidence: 99%
“…Generally, these data, however, often lose significance once selection bias of patients chosen for HDF therapy are removed (Locatelli et al 2017). There is evidence from a number of individual studies that HDF can be beneficial for individual patients (Davenport et al 2010, Oates et al 2011, Maduell et al 2013, Dey et al 2015, Hill et al 2017 and for this reason many units have made the therapy available to increasing numbers of HD patients in recent years. Most commonly reported benefits of HDF in these studies include; improved haemodynamic stability during treatment, improved blood pressure control, improved dialysis clearance (Kt/V), improved phosphate control (sometime with ability to reduce dose of phosphate binders) and often qualitative indications of improved quality of life.…”
Section: Hdf Evidence Basementioning
confidence: 99%